Religion in the Public Sphere: A Comparative Analysis of German, Israeli, American and International Law
XVI, 469 p.
Keywords: How closely correlated should church and state be? May a state recognize or dignify the role and meaning of religion at all, and if so can it treat different religious groups differently? This book intends to answer these questions through a portrayal and comparison of various legal orders including those of Germany, Israel, France and the USA. Some authors consider the issue of “church and state” from an international law perspective. The analyses are structured from both a state-institutional as well as from a fundamental rights and human rights perspective. Here the religious and secular freedoms are brought into focus. Whether, and how, these church-and-state aspects vary within divergent modern state contexts – and how they transnationally evolve – is also discussed.